The Accuracy of Approximate Solar Coordinates US Naval Observatory in Prayer Time Calculations - Nurussaadah, Annisa; M. Ihtirozun Niam; Sudirman L (Universitas Islam Negeri Mataram, 2024)
This study aims to test the accuracy of Approximate Solar Coordinates (ASC) data issued by the U.S. Naval Observatory (USNO) in calculating prayer times. The method used in this research is the comparative qualitative research method. The author compares the Sun declination and equation of time data obtained from the USNO ASC algorithm with Ephemeris Hisab Rukyat data for one year. From this research, it is found that the maximum difference between the Sun declination value from the ASC USNO algorithm compared to the Hisab Rukyat ephemeris is only 15 seconds of arc. While the maximum difference in the equation of time value is only around 2 seconds. The maximum difference in the calculation of prayer time between the two is only 2 seconds. Therefore, this ASC USNO data can be used as an alternative choice in calculating prayer times. Not only because the algorithm is quite concise, but the results obtained are also accurate for prayer times.